Exposure of pregnant women to tap water related activities. Issue 5 (16th April 2004) - Kaur, S; Nieuwenhuijsen, M J; Ferrier, H; Steer, P
Abstract : Background: Evidence for an association between exposure of pregnant women to chlorination disinfection by-products and adverse birth outcomes is inconsistent and inconclusive. Aims: To evaluate the use of a questionnaire in a population of pregnant women to assess their exposure to water, examine the validity of the questionnaire by a seven day diary, and to obtain a better understanding of the exposure of pregnant women to water in Central London. Methods: A total of 147 pregnant women were asked to complete a questionnaire. Information was requested on their exposure to water from cooking and washing up, showering and bathing, food and drink, and swimming. Demographic and socioeconomic information were also recorded. For validation purposes, women were asked to complete a seven day diary at home. Results: The average exposure duration was 338.5 min/week for cooking and washing up, 172.2 min/week for bathing and showering, and 67.9 min/month for swimming. The total fluid intake was 18.9 l/week of which, on average, 18% was cold tap water; 30% of this tap water was consumed outside the home. The correlation between questionnaire and diary data was generally good to very good, although women tended to overestimate their exposure in the questionnaire compared to the diary. Conclusions: Information was obtained on the daily exposure of pregnant women in Central London to chlorinated water at home, work, and elsewhere. The questionnaire was found to be a valid method to assess the exposure of pregnant women to water and the response rate was higher than for diaries.